'Being' a ventricular assist device recipient: A liminal existence. (October 2017) - Standing, Holly C.; Rapley, Tim; MacGowan, Guy A.; Exley, Catherine
Abstract: Ventricular assist devices (VADs) are playing an increasing role in the management of heart failure. VADs are mechanical circulatory devices that support or replace the function of a failing heart. Currently, VADs are only offered in theUnited Kingdom (UK) to patients waiting for a heart transplant; however, the use of these devices is likely to increase in the near future. Presently, there is a dearth of literature exploring the day-to-day realities of living with a VAD, which will become increasingly important as the role of VADs is increased. This paper adopts an interpretive phenomenological approach to uncover the experience of 'Being' a VAD recipient. Semi-structured interviews were conducted with 20 VAD recipients. The overarching theme is that life with a VAD is a liminal existence. This comprised four subthemes: the first examines how the VAD imposes limitations on recipients' lives that can precipitate a loss of identity; the second focuses on temporal disruptions, recipients' sense of time changes from authentic to inauthentic; the third explores how the VAD itself is liminal, it is positioned as temporary rather than as the 'answer' to the condition; and finally, we discuss VAD recipients' projections to the future and the possibility of an end to the experience of liminality. Highlights: Qualitative interviews with ventricular assist device (VAD) recipients. Uses phenomenology to explore the experience of 'Being' a VAD recipient. The VAD disrupts recipients' sense of time and identity. VAD recipients struggle to develop a new normality around the device. Future is focused on heart transplantation.